The voice of the voiceless : reading Luke 1:46-55 in the context of HIV/AIDS in response to Elisabeth Schüssler Fiorenza’s feminist theology - Kim, Elizabeth Min Hee (Stellenbosch : Stellenbosch University, 2013)
Thesis (MTh)--Stellenbosch University, 2013.